Isoprene as Lithiation Mediator: Synthesis of 2-Substituted 1-Alkylimidazole Derivatives - Martínez, Regina; Torregrosa, Rosario; Pastor, Isidro M.; Yus, Miguel (Synthesis, 2012)
The lithiation of different imidazoles bearing a primary (i.e., butyl, pentyl, dodecyl) or secondary (i.e., cyclohexyl, 1-methylheptyl) alkyl substituent on the nitrogen has been successfully achieved by means of an isoprene-mediated protocol. The subsequent reaction of the 2-lithioimidazole intermediates with different electrophiles leads to the formation of interesting 1,2-disubstituted imidazoles.
Keywords: imidazole derivatives; isoprene-mediated lithiation; lithium metal; nucleophilic addition; deprotonation